Thoracic Ultrasound in Cattle: Methods, Diagnostics, and Prognostics - Luis F. B. B. Feitoza; Brad J. White; Robert L. Larson (Veterinary Sciences)
Thoracic ultrasonography (TUS) has emerged as a critical tool in the diagnosis and management of respiratory diseases in cattle, particularly bovine respiratory disease (BRD), which is one of the most economically significant health issues in feedyard operations. The objective of this review is to explore TUS in veterinary medicine, including the historical development, methodologies, and clinical applications for diagnosing and prognosing respiratory diseases. This review also emphasizes the importance of operator training, noting that even novice operators can achieve diagnostic consistency with proper instructions. Ultrasound was introduced in the mid-20th century for back-fat thickness measurements; TUS has evolved to offer a non-invasive, real-time imaging modality that allows for the detection of lung and pleural abnormalities such as consolidations, pleural effusions, and B-lines. These features are vital indicators of respiratory disease, and their early identification through TUS can significantly improve clinical outcomes. Compared to traditional diagnostic methods like auscultation or radiography, TUS provides superior accuracy in detecting both subclinical and advanced respiratory conditions, particularly in high-risk populations. Furthermore, TUS has demonstrated strong prognostic value, with studies showing that the extent of lung consolidation correlates with higher relapse risk, reduced growth performance, and increased mortality.